Pengendalian Kualitas Kemasan Plastik Pouch Menggunakan Statistical Procces Control (SPC) di PT Incasi Raya Padang - Rendy Kaban (Jurnal Optimasi Sistem Industri, 2014)
PT Incasi Raya is one of the major companies in Indonesia which produce edible oils. One of the stages in the production activities are packaging products. Used packaging made of plastic material, with the capacity and different type. Plastic pouch is one of the few types of packaging used in the packaging of edible oils. Quality packaging affects the distribution of production to the consumer. If the packaging is damaged, then the product can not be distributed to consumers. Therefore, the quality of the packaging must be kept for the successful marketing of the product. One way to implement a quality control methods Statistical Processing Control (SPC). The data used in this study is a secondary data provided by the company. Data collected is the number of production reject every month in packaging activities. The data processing of the data collection that is making control map p. The results of data processing show that many reject the production of packaging that are outside the control limits. Data that are outside the control limits indicates there is a problem in the quality control of the company. Of all types of packaging, only one or two months of production reject packs that are in the control limits. This suggests that the dominant packaging reject each month of production is outside the control limits. Reject the production was analyzed using a causal diagram. Factors influencing the presence reject packaging production is based on the analysis of human, machine, environment, materials, and methods within the company. After analyzing of the causal diagram, the data is revision. Making a map of the proposed p controls the data that has been revised is the end result of the data processing is done. Quality control companies are advised to be on the boundary control such as control map p recommended.